1983
DOI: 10.1002/pad.4230030102
|View full text |Cite
|
Sign up to set email alerts
|

The role of public administrators in public policy making: Practice and prospects in Nigeria

Abstract: In Nigeria, as elsewhere, the role of the career bureaucracy in public policy making has constituted a subject of conflicting interpretation, practice, and prescription. Although higher public servants have always played a major part in shaping public policy, the extent of their involvement has ebbed and flowed in response to legal, structural, and political changes at the federal, state, and local government levels. In recent years, the exercise of policy making and implementing roles by public administrators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are evidences from scholarship to establish the importance of formulation antecedents and process as critical to policy successes in Nigeria (Olaiya, 2010a;Olaiya, 2010b;Ebienfa, 2009;Koehn, 1983;Aminu, Tella & Mbaya, 2012;Paki & Ebienfa;and Ugwuanyi & Chukwuemeka, 2013) To this end, and bearing in mind the need to formulate enduring public policies in the area of economic and socio-cultural rights, the study concluded on the following critical stance: (a) There is urgent need to promulgate laws that will serve as the backbones of policies on economic and social rights not only to ensure consistency but also to foster continuity; (b) there is also the need to be more constitutional in all aspects of the formulation of social right policies to prevent abuse in the highest possible regards and, most importantly, to ensure popularity of the policies as the constitution is the mother law that a good number of members of the society are familiar with; and the prevailing situation of lack of assertive position by the courts between the provisions of Section 6(6)c of the 1999 Constitution and Article 24 of the International Covenant on Economic and Social Rights (ICESCRs) should be resolved, either by outright amendment to the relevant part of the 1999 constitution or by the legislature exercising its power in Item 60(a) of the Exclusive Legislative List.…”
Section: Resultsmentioning
confidence: 99%
“…There are evidences from scholarship to establish the importance of formulation antecedents and process as critical to policy successes in Nigeria (Olaiya, 2010a;Olaiya, 2010b;Ebienfa, 2009;Koehn, 1983;Aminu, Tella & Mbaya, 2012;Paki & Ebienfa;and Ugwuanyi & Chukwuemeka, 2013) To this end, and bearing in mind the need to formulate enduring public policies in the area of economic and socio-cultural rights, the study concluded on the following critical stance: (a) There is urgent need to promulgate laws that will serve as the backbones of policies on economic and social rights not only to ensure consistency but also to foster continuity; (b) there is also the need to be more constitutional in all aspects of the formulation of social right policies to prevent abuse in the highest possible regards and, most importantly, to ensure popularity of the policies as the constitution is the mother law that a good number of members of the society are familiar with; and the prevailing situation of lack of assertive position by the courts between the provisions of Section 6(6)c of the 1999 Constitution and Article 24 of the International Covenant on Economic and Social Rights (ICESCRs) should be resolved, either by outright amendment to the relevant part of the 1999 constitution or by the legislature exercising its power in Item 60(a) of the Exclusive Legislative List.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Adebayo (1979) observes that during 1966-1975, some State Governments had up to seven permanent secretaries that were stationed in the Military Governor's office and had the responsibility for almost the entire range of political, economic, administrative and industrial activities of the government. The military consciously drew top public servants deeper into policy-formulation responsibilities (Luckham, 1971;Koehn, 1983).…”
Section: The Roles Of Bureaucracymentioning
confidence: 99%
“…The direct involvement of bureaucrats in the military junta's policy-making process was initiated by Ironsi and advanced by Gowon (Asiodu, 1970;Aliyu, 1979;Adebayo, 1979;Koehn, 1983). This was attributed to the military juntas' lack of experience, their unwillingness to appoint ousted politicians to positions of responsibilities and the relatively low level of education many military personnel had (Koehn, 1983).…”
Section: The Roles Of Bureaucracymentioning
confidence: 99%
See 2 more Smart Citations